2015
DOI: 10.1021/acsami.5b04152
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Photoresponse of Amorphous In–Ga–Zn–O and Zinc Oxynitride Semiconductor Devices by the Extraction of Sub-Gap-State Distribution and Device Simulation

Abstract: Persistent photoconduction (PPC) is a phenomenon that limits the application of oxide semiconductor thin-film transistors (TFTs) in optical sensor-embedded displays. In the present work, a study on zinc oxynitride (ZnON) semiconductor TFTs based on the combination of experimental results and device simulation is presented. Devices incorporating ZnON semiconductors exhibit negligible PPC effects compared with amorphous In-Ga-Zn-O (a-IGZO) TFTs, and the difference between the two types of materials are examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 30 publications
4
80
0
Order By: Relevance
“…Studies on In and Zn-based multi-component metal oxides such as InGaZnO [2], InZnO [3], HfInZnO [4] and InZnSnO [5] have been constantly reported, focusing mainly on high field effect mobility and high stability with respect to bias, temperature and illumination stress. Since Ye et al reported on zinc oxynitride (ZnON) semiconductors in 2009 [6], semiconductors based on this compound have drawn attention due to several advantages such as high field effect mobility ($ 100 cm 2 /Vs) and device stability with respect to illumination [7][8][9][10]. Recently, studies on nitrogendoped ZnO have gained attention for various applications such as photo-electrochemical devices and photo-sensors involving the design of the material's optical band structure [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on In and Zn-based multi-component metal oxides such as InGaZnO [2], InZnO [3], HfInZnO [4] and InZnSnO [5] have been constantly reported, focusing mainly on high field effect mobility and high stability with respect to bias, temperature and illumination stress. Since Ye et al reported on zinc oxynitride (ZnON) semiconductors in 2009 [6], semiconductors based on this compound have drawn attention due to several advantages such as high field effect mobility ($ 100 cm 2 /Vs) and device stability with respect to illumination [7][8][9][10]. Recently, studies on nitrogendoped ZnO have gained attention for various applications such as photo-electrochemical devices and photo-sensors involving the design of the material's optical band structure [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Since Ye et al reported on zinc oxynitride (ZnON) semiconductors in 2009 [6], semiconductors based on this compound have drawn attention due to several advantages such as high field effect mobility ($ 100 cm 2 /Vs) and device stability with respect to illumination [7][8][9][10]. Recently, studies on nitrogendoped ZnO have gained attention for various applications such as photo-electrochemical devices and photo-sensors involving the design of the material's optical band structure [10][11][12][13]. Especially, nitrogen plays important roles when zinc oxynitride is formed.…”
Section: Introductionmentioning
confidence: 99%
“…22,23,28 Such photogenerated carriers are the source of photocurrent. 15,22,23,28 Using such photocurrents in metal oxide based TFTs (singe gate), the optical sensor-embedded interactive displays are demonstrated by several groups. 15,23 It has been reported that photosensing capability increases with the increasing subgap states (V O ).…”
mentioning
confidence: 99%
“…15,22,23,28 Using such photocurrents in metal oxide based TFTs (singe gate), the optical sensor-embedded interactive displays are demonstrated by several groups. 15,23 It has been reported that photosensing capability increases with the increasing subgap states (V O ). 23 The addition of oxygen during deposition passivates such subgap states existing near the valance band.…”
mentioning
confidence: 99%
See 1 more Smart Citation